Toll-like receptor 2 activation of early divided bovine embryo promotes its viability and development competence in vitro - Dongxue Ma; Ihshan Akthar; Taiyo Hashimoto; Mohamed A. Marey; Kazuya Kusama; Kazuhiko Imakawa; Masayuki Shimada; Akio Miyamoto (Scientific Reports)
Abstract Improving the quality and developmental competence of in vitro-produced (IVP) embryos is crucial for assisted reproductive technologies. Recently, we demonstrated that TLR2, an innate immune receptor, is expressed in bovine sperm and their activation improves fertilization and subsequent embryo development. However, its role in early embryo development is poorly understood. This study investigated the impact of activation of early embryonic TLR2 on IVP bovine embryo development. The immunofluorescence and western blot analyses confirmed robust TLR2 expression in early embryonic stages. Embryos were treated at 36 h post-insemination (hpi), with 100 ng/ml of TLR2 agonist and cultured in vitro and showed increased blastocyst rates and faster growth speed. Additionally, TLR2 activation slightly increased basal calcium levels and induced autophagy while suppressing cathepsin B activity and DNA damage, leading to reduced apoptosis in embryos. Together, these findings indicate that embryo TLR2 is involved in embryo development competence via a slight increase in the basal cytosolic calcium and subsequent embryo metabolic activities, autophagy induction, and reduction of apoptosis levels. These results provide a promising approach for producing highly competent good-quality embryos for improving the efficiency of IVP bovine embryos.